2022
DOI: 10.1002/ls.1632
|View full text |Cite
|
Sign up to set email alerts
|

Tribology of dust‐stop seals of mixing machines

Abstract: Dust stop seals are widely used in powder and rubber mixing industries.Design of the sealing system requires a continuous supply of pressurised lubricant, which is not recycled because of the risk of contamination. There is also the potential of large volume leakage of oil due to poor sealing, increasing operational costs and necessitating remedial measures to avoid environmental protection. Furthermore, the seal faces are prone to failure in relatively short periods of time due to reduced gap and lubricant le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…In this regime, a thin lubricant layer known as the lubrication film carries most of the applied load. The contact of asperities also contributes to carrying the total load, which raises the surface temperature and causes wear, and on the other hand, changes the topography of the surface due to the plastic or elastoplastic deformation of asperities [29].…”
Section: Simulationmentioning
confidence: 99%
See 3 more Smart Citations
“…In this regime, a thin lubricant layer known as the lubrication film carries most of the applied load. The contact of asperities also contributes to carrying the total load, which raises the surface temperature and causes wear, and on the other hand, changes the topography of the surface due to the plastic or elastoplastic deformation of asperities [29].…”
Section: Simulationmentioning
confidence: 99%
“…Based on this equation, it can be concluded that the asperity pressure throughout the asperity region is equal to the overall contact pressure p m . If N a is considered the number of asperities on the surface with a nominal area A n , then the contact number of asperities can be achieved using the following relationship [29]:…”
Section: Simulationmentioning
confidence: 99%
See 2 more Smart Citations